EVALUATION OF THE THERAPEUTIC EFFECTS OF SALVIA ROSMARINUS ESSENTIAL OIL ON NERVOUS SYSTEM DISORDERS - Malina Mihaela Visternicu; Viorica Rarinca; Vasile Burlui; Alin Ciobica (Journal of Experimental and Molecular Biology)
Rosemary (Salvia rosmarinus) is an aromatic plant that has been used for centuries in traditional medicine for its remarkable therapeutic properties. Rosemary contains bioactive compounds with antioxidant, anti-inflammatory, and neuroprotective actions, and it is recognized for its beneficial effects on mental and cognitive health. This review explores the therapeutic potential of rosemary in alleviating nervous system disorders such as Alzheimer's disease (AD), major depressive disorder (MDD), epilepsy, Parkinson's disease (PD), addiction, and attention-deficit hyperactivity disorder (ADHD). Preclinical and clinical research suggests that rosemary extracts, through their active compounds, may enhance cognitive function, protect neurons from oxidative stress, and modulate neurotransmitters involved in cognitive and emotional processes. The findings indicate that rosemary could be a promising complementary therapy in managing nervous system disorders, offering significant benefits for mental and neurological health. However, further studies are needed to fully understand the efficacy and safety of long-term use.